2013
DOI: 10.30955/gnj.000579
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particles (UFP) and health effects. Dangerous. Like no other PM? Review and analysis

Abstract: The goal of the current review is to present and analyze the known information proposed and discussed the last few years about UFP and their possible health effects. It includes references from 1992 to 2008. It also includes references from some fundamental studies in the 1970's and 1980's. The review and analysis of the health hazards induced by ultrafine particle exposure focuses on the; classification and characteristics of suspended particulate matter (PM), features and properties of PM and, specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…There is an interesting and critical note in this regard, and it is related to the chemical composition of treatment, and from this view, they are in good agreement together. Based on the present data and earlier reports [31][32][33], ultrafine particles induce higher cell mortality and apoptosis than the larger ones. Previous reports were related to air pollution and cytotoxic materials, and the present investigation is related to the FTY-720 as a neuroprotective.…”
Section: Survival Proteins Assessmentsupporting
confidence: 82%
See 1 more Smart Citation
“…There is an interesting and critical note in this regard, and it is related to the chemical composition of treatment, and from this view, they are in good agreement together. Based on the present data and earlier reports [31][32][33], ultrafine particles induce higher cell mortality and apoptosis than the larger ones. Previous reports were related to air pollution and cytotoxic materials, and the present investigation is related to the FTY-720 as a neuroprotective.…”
Section: Survival Proteins Assessmentsupporting
confidence: 82%
“…However, the data associated with the environmental effects of ultrafine particles (<100 nm) on CNS show that inhaled ultrafine particles of air pollution exhibit a higher level of inflammation and cell mortality than the fine particles. It is eventually due to enhanced surface to volume ratio and absorption [31][32][33]. Gillespie et al demonstrated that although two fine and ultrafine air pollutions induce apoptosis of neural cells, inducible apoptosis derived from ultrafine particles was higher than fine particles [33].…”
Section: Cell Viabilitymentioning
confidence: 99%